1986
DOI: 10.1002/1097-0142(19860415)57:8<1515::aid-cncr2820570813>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Liver cell dysplasia in cirrhosis. A serologic and immunohistochemical study

Abstract: Liver cell dysplasia (LCD) was investigated for hepatitis B virus (HBV) markers, alpha-fetoprotein (AFP) and ferritin by serologic and immunohistochemical methods in 101 patients with cirrhosis. LCD was found in 30 cases (29.7%), with the highest incidence in cases of posthepatitic cirrhosis (67%). In the group of dysplastic cirrhosis (DC) 46.6% of the patients had active HBV infection (hepatitis B surface antigen [HBsAg] serum positivity) compared with 7% of the patients with nondysplastic cirrhosis (NDC) (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…This feature that is consistently reported in different studies, either on liver biopsies or on surgical resections, has been taken to support premalignancy, given the multifocal hepatic carcinogenesis, or to disclaim it as a simple bystander phenomenon [14]. Another interesting feature of dysplasia is its persistence over time, as reported in consecutive liver biopsies [10,15]. Such a feature is biologically consistent either with a lesion uncommitted to die or with an age-related change.…”
Section: Morphological Description Of Lccmentioning
confidence: 71%
See 2 more Smart Citations
“…This feature that is consistently reported in different studies, either on liver biopsies or on surgical resections, has been taken to support premalignancy, given the multifocal hepatic carcinogenesis, or to disclaim it as a simple bystander phenomenon [14]. Another interesting feature of dysplasia is its persistence over time, as reported in consecutive liver biopsies [10,15]. Such a feature is biologically consistent either with a lesion uncommitted to die or with an age-related change.…”
Section: Morphological Description Of Lccmentioning
confidence: 71%
“…Some papers suggested that LCC is mostly negative for tissue HBsAg/HBcAg [15,29]. Given that loss of expression of viral proteins is a common feature of malignant hepatocytes, possibly due to HBV integration into the host DNA, more objective data on HBV physical status and protein expression should be provided to address putative similarities between dysplastic and malignant hepatocytes in HBV-related cirrhosis.…”
Section: Hbsagmentioning
confidence: 97%
See 1 more Smart Citation
“…This work was presented in part at the 25th meeting of the European Association for the Study of the Liver in Budapest, [3][4][5][6] October 1990.…”
Section: Commentmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Only a few prospective studies have ing intensive screening for HCC. Liver cell dysplasia 32,33,[37][38][39] has been considered prebeen performed to determine the predictive factors for the occurrence of HCC on cirrhotic liver. [27][28][29][30] However, cancerous.…”
mentioning
confidence: 99%